The terraformers eaudiobook - Newitz, Annalee (Macmillan Audio, 2023)
This program includes original sound design. From science fiction visionary Annalee Newitz comes The Terraformers , a sweeping, uplifting, and illuminating exploration of the future. Destry's life is dedicated to terraforming Sask-E. As part of the Environmental Rescue Team, she cares for the planet and its burgeoning eco-systems as her parents and their parents did before her. But the bright, clean future they're building comes under threat when Destry discovers a city full of people that shouldn't exist, hidden inside a massive volcano. As she uncovers more about their past, Destry begins to question the mission she's devoted her life to, and must make a choice that will reverberate through Sask-E's future for generations to come. A science fiction epic for our times and a love letter to our future, The Terraformers will take you on a journey spanning thousands of years and exploring the triumphs, strife, and hope that find us wherever we make our home. "Brilliantly thoughtful, prescient, and gripping."—Martha Wells, The Murderbot Diaries Also by Annalee Newitz Autonomous The Future of Another Timeline A Macmillan Audio production from Tor Books.